Unilateral Vocal Cord Paralysis Post Covid-19 Infection: A Case Report - Paudyal, Anish; Karki, Sphurna; Bhatta, Sachin; Lamichhane, Sashwat Raj; Dhungana, Anup (Nepal Medical College Journal, 2023)
Late-onset neurological complication post-SARS-COV-2 infection is an atypical feature of COVID-19 infection. Vocal cord paralysis is one such complication that can cause symptoms ranging from mild hoarseness of voice to severe dyspnoea requiring mechanical ventilation. In this case report, we describe a 51 years old male with sudden onset of hoarseness of voice six months after recovery from COVID-19 pneumonia without endotracheal intubation and no history of respiratory or any other new illness in between. Nasopharyngolaryngoscopy revealed the left vocal cord paralysis, and a CT scan showed fibrosis, an air cyst in the upper lobe of the left lung, and bilateral lung diffuse ground glass opacity. There was no significant improvement in voice on treatment with prednisolone for nine days and speech therapy. Thus, unilateral vocal cord palsy can present as sequelae of COVID-19 pneumonia.